Peranan Perdagangan Internasional Terhadap Ekspor Rempah-Rempah di Indonesia - J, Jumawan; Prasetyo, Andhika Rifki; Munthe, Anselinus Kevin; Al-Baihaqi, Iqbal; Nurazizah, Rizty Dwi; Salfaniz, Sahira (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The country's economy relies heavily on exports. The country's export performance has a greater impact on economic growth. From 2012 to 2016, Indonesia's exports continued to decline. Import-export activities can also reduce unemployment. In conditions like this, Indonesia absolutely needs to make strategic efforts. One thing that can be done is to increase exports. Indonesia is one of the world's top five spice producers, producing cinnamon, cloves, nutmeg, pepper and vanilla - so it has a lot of room for expansion. The aim of this research is to find out whether spice exports in Indonesia can be optimal as economic growth increases and also to find out whether competition with other spice producing countries in the international market can affect spice exports in Indonesia. This type of research is qualitative research. Exports and imports are used to evaluate a country's progress towards economic development. Having a strong free trade policy allows countries to obtain cheaper raw materials and encourages economic expansion. Import and export indicators are also used to assess the progress of a country's economic development.